Education and awareness: keys to solid waste reduction - Laberiano Andrade-Arenas; Elizabeth Liñan Espinoza (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
In the research, education, and awareness were focused on as essential pillars to successfully address the problem of reducing solid waste. The objective is to implement educational and awareness solutions within the community to encourage a substantial change in behavior toward the reduction of solid waste. The design thinking methodology was applied to develop effective solutions. To measure the level of public awareness, we conducted interviews using the Atlas ti22 which allowed us to triangulate with the surveys that revealed that 60% of those surveyed agreed with the policies regarding environmental impact, 55% agreed that the authorities take preventive measures regarding public health and 58% stated that the participation of the citizens in recycling programs. Then, innovative prototypes were developed that satisfied the real needs of users and experts in their evaluation, thus laying a solid foundation. It was concluded that citizens as well as authorities must be aware that by working collaboratively, we can contribute to society.